Revision of the nitidus species group of the bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea) - Mack, Anne; Kuhlmann, Michael (European Journal of Taxonomy, 2023)
The nitidus species group of the bee genus Scrapter Lepeletier & Serville, 1828 is redefined, revised and 15 species are described as new for science: S. caeruleus sp. nov. ♀, S. confusus sp. nov. ♀♂, S. convexoides sp. nov. ♂, S. convexus sp. nov. ♀♂, S. crassipunctatus sp. nov. ♀♂, S. felicis sp. nov. ♀♂, S. flavipunctatus sp. nov. ♀♂, S. imparilis sp. nov. ♀♂, S. littoralis sp. nov. ♀, S. longicornis sp. nov. ♂, S. montanus sp. nov. ♀♂, S. mpumalangensis sp. nov. ♀♂, S. obtusus sp. nov. ♀♂, S. perpunctatulus sp. nov. ♂ and S. variabilis sp. nov. ♀♂. The previously unknown males of S. divergens (Friese, 1925), S. semirufus Cockerell, 1932 and S. perpunctatus Cockerell, 1933 are described for the first time. All currently known 28 species of the S. nitidus species group are redescribed, imaged and included in a key to facilitate their identification.